Global marketing contemporary theory, practice, and cases - Alon, Ilan; Jaffe, Eugene D.; Vianelli, Donata (McGraw-Hill/Irwin, 2013)
Provides an international and comparative perspective to the study of marketing. This title includes examples that are provided from across the continents encompassing small and medium enterprises (SMEs).